2020
DOI: 10.1038/s41467-019-14092-3
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbon formation chemistry in a plasma jet revealed by IR-UV action spectroscopy

Abstract: Large polycyclic aromatic hydrocarbons (PAHs) are the most abundant complex molecules in the interstellar medium; however, their possible formation pathways from small molecular species are still elusive. In the present work, we follow and characterize the formation of PAHs in an electrical discharge, specifically the PAH naphthalene in a molecular beam of argon. The fragments, products and reaction intermediates are unambiguously structurally identified by mass-selective IR-UV spectroscopy combined with quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 65 publications
4
66
0
Order By: Relevance
“…The interactions governing cluster formation of small PAH molecules are receiving significant interest from both theoreticians and experimentalists [1][2][3][4][5][6][7]. The π-π stacking and/or CH-π interactions that may be present in these archetypal complexes can have important contributions to the structure of molecules or molecular complexes of interest in astrochemistry [8][9][10][11][12][13], biochemistry soot formation, and to the astrochemistry community because they form a link between isolated molecules and carbonaceous grains [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions governing cluster formation of small PAH molecules are receiving significant interest from both theoreticians and experimentalists [1][2][3][4][5][6][7]. The π-π stacking and/or CH-π interactions that may be present in these archetypal complexes can have important contributions to the structure of molecules or molecular complexes of interest in astrochemistry [8][9][10][11][12][13], biochemistry soot formation, and to the astrochemistry community because they form a link between isolated molecules and carbonaceous grains [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…79,80 Polycyclic aromatic hydrocarbons are oen considered for the design of new organic lightemitting diode materials, eld-effect transistors or photovoltaics. 3,7,81 Their electronic properties make these molecules not only relevant for optoelectronic applications, but also for other research areas such as astrochemistry 82 and atmospherical chemistry. 83 The excitation spectra are predicted with the ML model trained on PBE0 orbital energies of the OE62 data set (denoted as ML(PBE0)) and the D-ML model trained on the difference of the ML(PBE0) model and the G0W0@PBE0 values of 4k datapoints of the GW5000 data set.…”
Section: Prediction Of Energy Levels and Photoemission Spectra Of Functional Organic Moleculesmentioning
confidence: 99%
“…The HACA mechanism produces mostly cyclopenta‐fused PAHs (Kislov et al., 2013). Another study provided alternatives to the HACA mechanism by identifying intermediates containing acetylene and diacetylene side chains in the formation of larger PAHs with up to four rings (Lemmens, Rap, Thunnissen, Willemsen, & Rijs, 2020). The experimental results indicated that growth of one of the smallest PAHs, NAP, would result in the formation of phenanthrene (Phe) and pyrene (Pyr).…”
Section: Mechanisms Of Pah Formation In Foodmentioning
confidence: 99%